Test 1

4 dx − 2x2

Name:

Evaluate each of the following integrals: 1. x3

Solution. The denominator factors as x2 (x − 2), so try the partial fraction decomposition A B 4 C = + 2+ − 2) x x x−2

x2 (x

(The first term is needed because of the repeated root.) Clearing denominators, we have

4 = 0x2 + 0x + 4 = Ax(x − 2) + B(x − 2) + Cx2 = Ax2 − 2Ax + Bx − 2B + Cx2 so we have the system of equations 0=A+C 0 = −2A + B 4 = −2B so B = −2, A = −1 and C = 1. Thus we integrate 1 2 2 1 dx = − ln |x| + + ln |x − 2| + C − − 2+ x x x−2 x (Note that
1 x2

dx =

x−2 dx =

x−1 −1

=

−1 ) x

2.

sin−1 x dx

As mentioned in class, integrating any inverse function is really an integration by parts in disguise: Solution 1. Let u = sin−1 x and dv = dx. Then du = integral becomes
√ 1 1−x2

and v = x. The

x sin−1 x −

√ x √ dx = x sin−1 x + 1 − x2 + C 1 − x2

The last integral above can be solved by making the u-substitution u = 1 − x2 and du = −2x dx (or a trig sub). Solution 2. Let y = sin−1 x. Then x = sin y and dx = cos y dy. Substituting in, the integral becomes √ y cos y dy = y sin y+cos y+C = sin−1 x·x+cos(sin−1 x)+C = x sin−1 x+ 1 − x2 +C The first step is a basic integration by parts and the last step comes from drawing a right triangle with one angle θ = sin−1 x, labeling sides and finding cos θ.
e

3.
1

√ t ln t dt √ t dt. Then du = 1 , v = 2 t 2 t 3
3

Solution. Integrate by parts with u = ln t and dv = and the (indefinite) integral becomes 2 3 2 t 2 ln t − 3 3 t2
3

2 3 2 1 dt = t 2 ln t − t 3 3 2 3 4 3 = t 2 ln t − t 2 + C 3 9

t 2 dt

1

Plugging in the bounds, the definite integral is 4 3 2 4 2 3 4 2 3 ( e 2 ln e − e 2 ) − ( ln 1 − ) = e 2 + 3 9 3 9 9 9 since ln e = 1 and ln 1 = 0.
π

4.
0

sin2 θdθ

1 Solution. Use the identity sin2 θ = 2 (1 − cos 2θ).

1 2

π

1 − cos 2θ dθ =
0

1 sin 2θ θ− 2 2

π 0

=

1 π (π − 0) − (0 − 0) = 2 2

5.

sec4 θ tan5 θ dθ

Solution 1. Let u = tan θ, so du = sec2 θ dθ. Rewrite the integral as sec2 θ tan5 θ sec2 θ dθ = = (u2 + 1)u5 du = u7 + u5 du = (tan2 θ + 1) tan5 θ sec2 θ dθ u8 u6 tan8 θ tan6 θ + +C = + +C 8 6 8 6

Solution 2. Let u = sec θ, so du = sec θ tan θ dθ. Rewrite the integral as sec3 θ tan4 θ sec θ tan θ dθ = = u3 (u2 − 1)2 du = = sec3 θ(sec2 −1)2 sec θ tan θ dθ u7 − 2u5 + u3 du

u3 (u4 − 2u2 + 1) du =

sec8 θ sec6 θ sec4 θ u8 2u6 u4 − + +C = − + +C 8 6 4 8 3 4

6.

sin θecos θ dθ

Solution. Let u = cos θ, du = − sin θ and sin θecos θ dθ = − eu du = −eu + C = −ecos θ + C

x3 dx to a trig integral. Simplify 9 − x2 as much as possible. Bonus: Complete the integral. 7. Make a trig substitution to convert √ Solution. Substitute x = 3 sin θ. Then dx = 3 cos θdθ and the integral becomes 27 sin3 θ 9 − 9 sin θ since
2

3 cos θ dθ =

27 sin3 θ 3 cos θ dθ = 3 cos θ

27 sin3 θ dθ

√ 9 − 9 sin2 θ = 3 1 − sin2 θ = 3 cos2 θ = 3 cos θ.

Bonus Solution. Note that sin3 θ = sin2 θ sin θ = (1 − cos2 θ) sin θ and letting u = cos θ and du = − sin θ dθ,

27

(1 − cos2 θ) sin θ = −27
√ 9−x2 3

1 − u2 du = 27(

u3 − u) + C = 9 cos3 θ − 27 cos θ + C 3

sin θ = x , so cos θ = 3 is

by drawing a right triangle. Plugging in, the integral

3 √ (9 − x2 ) 2 − 9 9 − x2 + C 3

8. After substituting x = 2 sec θ into θ+

f (x) dx, you have found that

f (x) dx =

1 cos(2θ) + C. Express this solution in terms of x. Simplify as much as possible. 2 Bonus: What is f (x)? Solution. sec θ = x so θ = sec−1 ( x ). By drawing a right triangle, we find that 2 √2 2 2 2 2 4 8 cos θ = x and sin θ = xx−4 . Thus cos 2θ = cos2 θ −sin2 θ = x2 − x x−4 = 8−x = x2 −1. 2 x2 1 8 1 Plugging these in, θ + 2 cos(2θ) + C = sec−1 x + 1 x2 + 2 + C = 2 sec−1 x + where C =
1 2

4 +C x2

+ C is a new arbitrary constant.
4 f (x) dx = sec−1 x + x2 + C, so f (x) = d (sec−1 dx

Bonus Solution. You know −2 4x )

x+

√ √ 1 x2 8 x2 − 1 x2 − 8 x2 − 1 √ = √ − 8x−3 = √ − = x3 x x2 − 1 x3 x2 − 1 x3 x2 − 1